Insecticidal and Antimicrobial Potential of the Volatile Oils of the Aerial Parts of Teucrium ramosissimum and Thymus hirtus subsp. algeriensis Growing in the South-West of Tunisia. Issue 6 (2nd November 2022) - Amari, Ramzi; Guesmi, Fatma; Saidi, Issam; Bouzenna, Hafsia; Khaled, Ichrak; Ali, Manel Ben; Hedfi, Amor; Alghamdi, Akram S.; Hfaiedh, Najla; Allagui, Mohamed Salah; Landoulsi, Ahmed
Abstract: The aim of this report was to investigate the possible lethal effect of Thymus and Teucrium essential oils against insects. Antimicrobial activity was evaluated by the disc diffusion assay. Relative repellency, fumigation and plant lethality on certain pest species were tested. A higher concentration of thyme (9.95 µL/cm 2 ) essential oil showed the greatest repellent effect against Tribolium confusum and Supella longipalpa . Exposure of pests to 2 µL thyme essential oil (EO) /l air resulted in 100 % mortality in 24 h. Thyme and Teucrium EO induced dose-response mortality of T. confusum larvae with LC50 values ⁣⁣of 45.22 and 38.10 µL/l air, respectively. Maximum lethality was recorded after 24 h and 48 h of exposure to the essence of T. algeriensis . Moreover, a total repellency effect was detected within 1 h of experiment at a concentration of 9.95 µL/cm 2 . Furthermore, complete lethality (100 %) of the nymph and adult of S. longipalpa (1˂ LT50 ˂6 h), T. confusum (LT50 ˂7 h) and the larvae of Blaps nefrauensis (1˂ LT50 ˂3 h) were observed. Additionally, thymol (0.3% w/w) was shown to induce moderate repellency and fumigant effect against studied insects. Overall, thyme and teucrium essential oils can be alternative botanical pesticides for these insects. But further experiments are needed to justify the insecticidal effect of essential oils used directly on T. confusum in cereal stores. As well, the experimental procedure using low doses of essential oil used for insecticidal potency should be repeated with high doses.